Revitalization of Dompu Traditional Industry as a Pillar of Creative Economy Based on Local Culture - Ahleyani, M.; Pratama, Andre Kurniawan; Sihombing, Ranjiv A. A; Astuti, Irma Widi; Nusantara, Althaf Fikar Harik (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2025)
This study aims to analyse the potential for revitalising traditional industries in Dompu Regency, West Nusa Tenggara, as a pillar of creative economic development based on the local culture